Coaches’ attitudes to injury and injury prevention: a qualitative study of Irish field hockey coaches - Catherine Blake; Eamonn Delahunt; Huw Rees; Ulrik McCarthy Persson; Colin Boreham; James Matthews (BMJ Open Sport & Exercise Medicine)
Translating injury prevention research into practice has been challenging, which may be due to a poor understanding of the contextual factors influencing the occurrence of injury. Coaches are key figure in sporting environments and hold pivotal roles in preventing injury. Therefore, the aim of this study was to investigate the attitudes of field hockey coaches to injury and injury prevention. Thirteen field hockey coaches from the amateur Irish Hockey League were interviewed. Reflexive thematic analysis led to three general dimensions comprised five higher-order themes, categorised from 16 lower-order themes. Coaches had positive beliefs regarding the benefits of injury prevention over injury management. However, they lacked the necessary knowledge and skills to successfully implement injury prevention strategies with players. Coaches recognised the importance of empowering players to self-manage training loads to promote injury prevention but acknowledged the need to protect younger players from increased loads. Many barriers to injury prevention were not controllable by coaches including fixture congestion and poor structuring of the sport’s domestic calendar. While coaches can play a key role in the implementation of injury prevention strategies, there is also a requirement to examine how system level barriers to injury prevention can be reduced.